Rarer in a Rare - Taksande, B (Medknow Publications & Media Pvt Ltd, 2013)
Though moya moya disease is a disease of Asian origin, it is one of the very rare causes of stroke in India. It is a rare disease mainly characterized by progressive cerebrovascular episode due to the slowly progressive stenosis of supraclinoid segment of bilateral internal carotid arteries, the anterior and the middle cerebral arteries, and very rarely, posterior cerebral arteries. We hereby report a case of a young female who presented to us with the psychiatric complaints and refractory headache since her childhood. Therefore, we are reporting rarer (headache and neuropsychiatric) manifestations in the rare (moya moya) disease.